Implementation of a Multi-Disciplinary Geriatric Oncology Clinic in Toronto, Canada - Ines B. Menjak; Khloe Campos; Mark Pasetka; Arlene Budden; Elaine Curle; Leslie Gibson; Ewa Szumacher; Rajin Mehta (Current Oncology, 2025)
Older adults with cancer tend to face more complex health needs than their younger counterparts. Patients > 65 years of age are recommended for comprehensive geriatric assessment (CGA) to capture and address age-related vulnerabilities. Access to geriatrics services is limited, and our baseline audit of geriatric referrals in 2019 from the cancer program revealed that only 30% of patients referred received a CGA. The aim of this study was to assess the implementation of a geriatric oncology (GO) clinic that employs CGA and determine patient outcomes. We conducted a retrospective cohort study at a single institution. Data collection included baseline characteristics, GO clinic findings and characteristics, recommendations/referrals, and emergency room (ER) visits/hospitalizations within 6 months of CGA. Descriptive statistics were used for analysis. A total of 100 patients were included, with a median (range) age of 80 (63–97) years; 70% were female, and the most common cancer type was breast (31%). Through the GO clinic, patients were seen in a timely manner, with a median of 3 weeks, compared to our historical baseline of 11 weeks. Cognitive decline (32%) and pre-treatment CGA (22%) were the most common reasons for referral, and the most common new diagnosis was cognitive impairment (65%). For pre-treatment CGA, 16 (48%) patients were deemed suitable for treatment and 10 (30%) were recommended for modified treatment; 34 (94%) referring physicians followed the recommendation. In addition, most (68%) patients received an allied health referral. One third of patients visited the ER and 30 (30%) patients were hospitalized. Overall, the GO clinic resulted in greater access to CGA in a timely manner, enhanced access to allied health, and assisted in treatment decision-making.